The World Resources Institute (WRI) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
The World Resources Institute (WRI)The World Resources Institute is a research and policy institute helping governments, the private sector, environmental and development organizations and others in their concern for meeting human needs while...